Occult intraocular foreign body presenting as squint - Takkar, Brijesh; Rathi, Anubha; Azad, Shorya (Nepalese Journal of Ophthalmology, 2016)
Background: We report a case of an occult retained intraocular foreign body detected four years after “forgotten” trauma. Case: A 23-year-old male presented with exodeviation and was referred as a case of epiretinal membrane. The anterior segment and adnexa were normal. Fundus examination revealed macular epiretinal membrane. An occult foreign body was localized in the retinal periphery. Imaging confirmed the diagnosis. Observation: Squint and epiretinal membrane may develop in cases of occult foreign bodies and may be the presenting sign years after trauma. Conclusion : A careful history of ocular trauma and thorough examination, complemented by radio imaging when needed, should be done in atypical cases.